Preparation method and application of modified fly ash floating beads and ultra-high performance concrete
By adding etching and modified ultra -fine coal ash drifting beads to ultra -high -performance concrete, the cracking problem caused by the self -contraction of concrete is solved, internal maintenance and self -repair, significantly improved the mechanical properties and durability of concrete, and promoted the promotion The resource utilization of solid waste.
Patent Information
- Application Number
- CN202410514390.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-04-26
AI Technical Summary
Ultra-high performance concrete is prone to self-shrinkage in the early stages, leading to serious cracking problems and affecting the appearance quality, safety and durability of the structure.
The internal maintenance and self -repairing effect is achieved by adding an ultra -fine coal ash drifting beads after etching and modified. Eclipsed the oxy ash drifting beads remove the surface closed film, exposed the internal porous structure, can absorb and release water, regulate the amount of waterization of water, reduce self -contraction; Secondary hydration to achieve self -repair.
A significant reducing the risk of self -contraction and cracking of ultra -high -performance concrete, improving the density and intensity of concrete, enhancing the pressure resistance and cracking resistance, prolonging the service life, and effectively using solid waste, reducing environmental pollution to environmental pollution Essence
Smart Images

Figure CN118388161B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new building materials, and specifically relates to a preparation method and application of modified fly ash floating beads and ultra-high performance concrete. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Ultra-High Performance Concrete (UHPC) has attracted widespread attention for its excellent mechanical properties, durability and fluidity, and is widely used in infrastructure fields such as high-rise buildings and bridges. However, due to its extremely low water-cement ratio (less than 0.20) and extremely high cement dosage, UHPC is prone to shrinkage in the early stages, which leads to serious cracking problems. The cracks caused by these cracking problems not only reduce the appearance quality of the structure, but also may become channels for the invasion of moisture, salt and other harmful substances, thereby accelerating the corrosion of steel bars and affecting the safety and durability of the structure. Therefore, how to effectively deal with the cracking problem caused by shrinkage in ultra-high performance concrete has become an important challenge restricting its application.
[0004] At present, internal curing technology and self-repairing technology can deal with the cracking problem. The materials commonly added in internal curing technology include: water-absorbing polymer (SAP). SAP can reduce the shrinkage and cracking of concrete, but its carrier and interface are weak areas of the microstructure, which seriously affects the density and mechanical properties of concrete, and the cost of SAP is relatively high. Similarly, self-repairing materials often rely on special additives or advanced materials, which may affect the performance of concrete itself; and the construction is complicated, the material cost is significantly increased, and it may even include harmful chemicals, which poses health and safety risks to workers and the environment, further limiting its large-scale application. Summary of the invention
[0005] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing and applying modified fly ash floating beads and ultra-high performance concrete. By adding ultra-fine fly ash floating beads that have been etched and modified, internal curing and self-repairing effects are achieved at the same time, which not only realizes the efficient utilization of floating bead solid waste resources, but also significantly improves the application performance and safety of UHPC in a green and sustainable way.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] In the first aspect, the present invention provides a modified fly ash floating beads, comprising: etched fly ash floating beads and a shell coating the outside of the etched fly ash floating beads, the particle size of the modified fly ash floating beads is 10 to 200 microns, and the thickness of the shell is 1 to 5 microns; the etched fly ash floating beads inside the shell are in a saturated state, and the shell is made of the following raw materials in parts by mass: 160 to 180 parts of cement and 20 to 30 parts of silica fume.
[0008] In a second aspect, the present invention provides a method for preparing the modified fly ash floating beads, comprising the following steps:
[0009] S1. After etching the fly ash floating beads with a corrosive solution, the fly ash floating beads in the corrosive solution are collected, washed, dried, filtered and dried to obtain etched fly ash floating beads;
[0010] S2. After the etched fly ash floating beads are fully saturated with water, the saturated etched fly ash floating beads, cement, silica fume, a water reducing agent and water are mixed and stirred to obtain a modified fly ash floating bead slurry;
[0011] S3. Spread the modified fly ash floating beads slurry flat and dry it to obtain the modified fly ash floating beads, and sieve the modified fly ash floating beads to obtain the modified fly ash floating beads.
[0012] In a third aspect, the present invention provides an ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0013] 430-574 parts of cement, 123-133 parts of fly ash, 99-109 parts of silica fume, 945-955 parts of fine aggregate, 4-5 parts of water reducer, 157-167 parts of water, 45-55 parts of fiber, 48-92 parts of etched fly ash floating beads and 96-195 parts of the above-mentioned modified fly ash floating beads.
[0014] In a fourth aspect, the present invention provides a method for preparing the above-mentioned internally cured and self-repairing ultra-high performance concrete, comprising the following steps:
[0015] S4, mixing cement, fly ash, silica fume, fine aggregate, etched fly ash floating beads and water mixed with a water reducing agent to obtain a first mixed slurry;
[0016] S5, adding modified fly ash floating beads and fibers to the first mixed slurry, stirring and mixing, to obtain a second mixed slurry;
[0017] S6. Casting and curing the second mixed slurry to obtain internally cured and self-repairing ultra-high performance concrete.
[0018] In a fifth aspect, the present invention provides the application of the above-mentioned ultra-high performance concrete in underground engineering in water-rich strata.
[0019] The beneficial effects of the present invention are:
[0020] 1. The present invention provides a method for modifying ultrafine fly ash floating beads. Only through soaking, stirring and drying, etched fly ash floating beads with internal curing function can be quickly prepared. After slurrying and drying, modified fly ash floating beads with self-repairing function can be prepared. Two additives for the cracking problem of ultra-high performance concrete are prepared using one raw material. The operation is simple and easy, and the two additives complement each other in function. It is easy to carry out large-scale production and application on the existing concrete production line, providing an efficient and economical solution for the engineering practice of ultra-high performance concrete.
[0021] 2. The etched fly ash floating beads used in the present invention remove the closed film on the surface of the fly ash floating beads, revealing the porous structure inside. These etched fly ash floating beads can absorb and release water during the early hydration reaction, effectively regulating the amount of water participating in the hydration reaction inside the concrete, effectively reducing early self-shrinkage, and avoiding the generation of cracks. At the same time, these gradually released water improves the compactness and strength of ultra-high performance concrete. A layer of solidified cement slurry film is added to the surface of the modified fly ash floating beads. When cracks appear in the concrete, its internal stress can break this layer of cement slurry film, release the water pre-stored in the saturated etched fly ash floating beads inside, promote secondary hydration, and effectively realize concrete self-repair. The double crack treatment measures significantly improve the compressive strength and crack resistance, which is of great significance for improving the structural safety and extending the service life of ultra-high performance concrete.
[0022] 3. The present invention effectively utilizes the solid waste of coal-fired power plants, namely ultrafine fly ash beads, and converts them into high-value building material additives. This resource utilization not only reduces the environmental pollution of industrial waste, but also promotes environmental friendliness and resource conservation in the building materials industry, and has important environmental value and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 It is a schematic diagram of the treatment process of ultrafine fly ash floating beads in Example 1 in a specific implementation manner of the present invention;
[0025] Figure 2 It is the shrinkage value-curing time curve of each sample in the specific implementation manner of the present invention. DETAILED DESCRIPTION
[0026] A typical embodiment of the present invention provides a modified fly ash floating beads, comprising: etched fly ash floating beads and a shell coated on the outside of the etched fly ash floating beads, the particle size of the modified fly ash floating beads is 10 to 200 microns, and the thickness of the shell is 1 to 5 microns; the etched fly ash floating beads inside the shell are in a saturated state, and the shell is made of the following raw materials in parts by mass: 160 to 180 parts of cement and 20 to 30 parts of silica fume.
[0027] Through the above settings, modified fly ash floating beads with self-repairing function are prepared. When cracks appear in the concrete, the internal stress can break the cement slurry film, release the water pre-stored in the saturated etched fly ash floating beads inside, promote secondary hydration, and effectively realize concrete self-repair.
[0028] Optionally, the particle size of the etched fly ash floating beads is 10 to 200 μm, the silicon dioxide content is greater than 50%, and it has a certain cementing activity and can be tightly combined with the cementitious material in the shell to form an appropriate hardness to prevent the shell from being damaged during the concrete mixing and pouring process. The particle size in this range is compatible with the microscopic void size in the concrete. The fine particle size can be evenly distributed and filled into all the microscopic pores of the concrete matrix material, thereby repairing all-round cracks in the concrete, and helping to improve the compressive strength and durability of the concrete, and improve the workability and fluidity of the concrete.
[0029] Optionally, the cement is 52.5 ordinary Portland cement, which has good compatibility with the polycarboxylic acid-based water reducer to form a slurry with good fluidity during the preparation process.
[0030] Optionally, the mass percentage of silicon dioxide in the silica fume is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 .
[0031] A typical embodiment of the present invention provides a method for preparing the modified fly ash floating beads, comprising the steps of:
[0032] S1. After etching the fly ash floating beads with a corrosive solution, the fly ash floating beads in the corrosive solution are collected, washed, dried, filtered and dried to obtain etched fly ash floating beads;
[0033] S2. After the etched fly ash floating beads are fully saturated with water, the saturated etched fly ash floating beads, cement, silica fume, a water reducing agent and water are mixed and stirred to obtain a modified fly ash floating bead slurry;
[0034] S3. Spread the modified fly ash floating beads slurry flat and dry it to obtain the modified fly ash floating beads, and sieve the modified fly ash floating beads to obtain the modified fly ash floating beads.
[0035] Optionally, in S1, the etching solution is prepared by mixing an acidic solution with a soluble fluoride to obtain a 1.0 M NH 4 A hydrofluoric acid etching solution consisting of 1.2M F and 1.2M HCl.
[0036] Optionally, in S1, the fly ash floating beads are ultrafine fly ash floating beads, which refer to hollow fly ash particles produced in the process of coal combustion in coal-fired power plants, and single-cavity hollow fly ash spheres obtained from the solid waste generated after coal combustion. The shell itself is porous but is sealed by a thin layer of glass-crystalline film; the particle size of the ultrafine fly ash floating beads is 10 to 200 microns, and the content of silica in the solid waste is greater than 50%.
[0037] Optionally, in S1, the method for preparing etched fly ash floating beads comprises:
[0038] S1-1, using 1.0M NH4F and 1.2M HCL to prepare a hydrofluoric acid corrosion solution, immerse the dry fly ash floating beads in the corrosion solution, stir and let stand, and collect the corroded fly ash floating beads that sink to the bottom; in this process, the closed membrane on the surface of the ultrafine fly ash floating beads is removed by chemical etching technology, revealing its internal porous structure so that it can store water, and the floating beads sink to the bottom, indicating that the closed membrane has been opened;
[0039] S1-2. Rinse the corroded fly ash beads that have sunk to the bottom with clean water and dry them. Then, place them in clean water, stir and separate them into layers, and filter to remove the damaged beads in the lower layer and the beads filled with debris. Collect the perforated beads in the upper layer, and then repeat the washing-drying-stirring in clean water-filtration for several times to obtain the etched fly ash beads to be dried. In this process, the corrosive liquid in the beads that have sunk to the bottom is removed, and the broken beads are also removed, so that the remaining beads have basically the same water absorption rate.
[0040] S1-3, vacuum drying the etched fly ash floating beads to obtain etched fly ash floating beads.
[0041] Preferably, in S1-1, the dried fly ash floating beads are immersed in the corrosion solution and stirred at a speed of 120 to 150 rpm for 8 to 10 minutes;
[0042] In S1-2, the corroded ultrafine fly ash floating beads in the lower layer are collected, and they are continuously rinsed with clean water, and the process is repeated 5 to 8 times, and then they are placed in an oven at 110° C. and dried for 24 hours; the dried ultrafine fly ash floating beads are placed in clean water, stirred at 120 to 150 rpm for 6 hours with a stirrer, and then filtered with a filter screen, and the perforated floating beads in the upper layer are retained;
[0043] Optionally, in S2, the water reducing agent is a polycarboxylic acid-based high-performance water reducing agent with a pH value of about 7.5 and a water reduction rate of more than 30%.
[0044] Optionally, in S2, the raw materials are mixed in the following proportions by mass: 160-180 parts of cement, 35-40 parts of saturated ultrafine fly ash beads, 20-30 parts of silica fume, 80-120 parts of water and 2-2.5 parts of water reducing agent.
[0045] Optionally, in S2, the saturation method includes: placing the etched ultrafine fly ash beads into a container, keeping the water level higher than the surface of the beads, stirring at a speed of 20 to 50 r / min for 8 to 10 minutes, and standing for 24 to 48 hours.
[0046] Optionally, a mixer is used for stirring in S2, the speed of the mixer is 120-150 r / min, and the stirring time is 90-120 s.
[0047] Optionally, in S3, the filter mesh number is 200 meshes.
[0048] A typical embodiment of the present invention provides an ultra-high performance concrete, which is prepared from the following raw materials in parts by weight:
[0049] 430-574 parts of cement, 123-133 parts of fly ash, 99-109 parts of silica fume, 945-955 parts of fine aggregate, 4-5 parts of water reducer, 157-167 parts of water, 45-55 parts of fiber, 48-92 parts of etched fly ash floating beads and 96-195 parts of the above-mentioned modified fly ash floating beads.
[0050] Optionally, the total mass fraction of cement, etched fly ash floating beads and modified fly ash floating beads is a set value of 712 to 722 parts, preferably 717 or 718 parts.
[0051] Optionally, the cement is 52.5 ordinary Portland cement, which has good compatibility with polycarboxylic acid-based water reducer.
[0052] Optionally, the mass percentage of silicon dioxide in the silica fume is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 .
[0053] Optionally, the fly ash is Class I fly ash, with a combustion vector less than 3.0% and a specific surface area greater than 1000cm 2 / g; its ingredients include silicon oxide and aluminum oxide, which has high hardness and can improve strength.
[0054] Optionally, the fine aggregate is river sand or quartz sand, with a fineness modulus of 2.3 to 3.0, a particle size of 0.075 to 0.35 mm, and an average particle size of 0.2 mm.
[0055] Optionally, the water reducer is a polycarboxylate water reducer.
[0056] Optionally, the fiber is one or more of polypropylene fiber and polyester fiber, the fiber shape is wavy, and the length is 6 mm to 12 mm.
[0057] Among the above components, the etched fly ash beads expose the pore structure on their shells, and the size of the pores on their surface can control the rate of water diffusion; since the etched fly ash beads are added in a dry state, these pores can absorb water during the concrete pouring process, and gradually release water during the hydration process, providing continuous internal maintenance for the concrete, significantly reducing the risk of self-shrinkage and cracking of ultra-high performance concrete. The surface of the modified fly ash beads is covered with a cement slurry film. When cracks occur, the internal stress level increases, causing the cement slurry film to rupture, releasing stored water, stimulating secondary hydration to fill the cracks, self-repairing and strengthening the durability of the material, and taking double crack treatment measures for ultra-high performance concrete. At the same time, the release of water provides sufficient water for the cement hydration reaction, promotes the formation of more hydration products, enhances the density and mechanical properties of the concrete, and especially improves the compressive strength and crack resistance.
[0058] A typical embodiment of the present invention provides a method for preparing the above-mentioned ultra-high performance concrete, comprising the following steps:
[0059] S4, mixing cement, fly ash, silica fume, fine aggregate, etched fly ash floating beads and water mixed with a water reducing agent to obtain a first mixed slurry;
[0060] S5, adding modified fly ash floating beads and fibers to the first mixed slurry, stirring and mixing, to obtain a second mixed slurry;
[0061] S6. Casting and curing the second mixed slurry to obtain internally cured and self-repairing ultra-high performance concrete.
[0062] Optionally, in S4, the raw materials are added into a mixer and stirred at a speed of 60 r / min for 3 min to obtain a first mixed slurry.
[0063] Optionally, in S5, the mixer stirs at a speed of 120 r / min for 3 min to obtain a second mixed slurry.
[0064] Optionally, in S6, standard curing is adopted, the formwork is removed after pouring for 1 day, and then the curing is carried out at a temperature of 20±2℃.
[0065] Example 1
[0066] Preparation of modified fly ash floating beads, such as Figure 1 As shown, the following steps are included:
[0067] Take the dried fly ash beads and observe them under a microscope. The surface is dense and there are no obvious cavities. Use 1.0M NH4F and 1.2M HCL to prepare a hydrofluoric acid corrosion solution. Immerse the dried fly ash beads in the corrosion solution and stir at a speed of 120-150rpm for 8-10min. It is observed that no less than 90% of the ultrafine fly ash beads are deposited at the bottom of the container.
[0068] Collect the corroded ultrafine fly ash floating beads in the lower layer, rinse them continuously with clean water, repeat 5 to 8 times, and then put them into an oven at 110°C for 24 hours, turning them over at least once during the period to ensure that the ultrafine fly ash floating beads can be fully dried; place the dried ultrafine fly ash floating beads in clean water, use a stirrer to stir at a speed of 120 to 150 rpm for 6 hours, and then filter them with a filter screen to retain the perforated floating beads on the upper layer, and then repeat "washing-drying-stirring in clean water-filtration" to obtain etched fly ash floating beads with internal curing function. Microscopic observation shows that the etched fly ash floating beads collected at this time still maintain a spherical shape, but there are obvious cavities distributed on the surface, and these cavities lead to the single-cavity hollow area inside the floating beads;
[0069] The etched fly ash floating beads are fully saturated with water, and placed in a cement mortar mixer according to the following mass proportions: 170 parts of cement, 38 parts of saturated ultrafine fly ash floating beads, 25 parts of silica fume, 100 parts of water, and 2.2 parts of water reducing agent, and stirred to mix thoroughly;
[0070] The ultrafine fly ash floating beads wrapped by the slurry are spread out and dried, and the ultrafine fly ash floating beads coated with slurry after drying are sieved through a 200-mesh sieve to obtain modified ultrafine fly ash floating beads with self-repairing function.
[0071] Example 2
[0072] An internally cured and self-repairing ultra-high performance concrete, the raw materials comprising the following raw materials in parts by weight: 48 parts of etched fly ash floating beads, 96 parts of modified fly ash floating beads, 574 parts of cement, 128 parts of fly ash, 104 parts of silica fume, 950 parts of sand, 4.5 parts of water reducer, 162 parts of water and 50 parts of polypropylene fiber;
[0073] Among them, the etched fly ash floating beads and the modified fly ash floating beads are both prepared by Example 1.
[0074] In this embodiment, the total mass fraction of cement, etched fly ash floating beads and modified fly ash floating beads is 718 parts, and the mass fraction ratio of etched fly ash floating beads to modified fly ash floating beads is 0.5.
[0075] The preparation steps are as follows: first, etched fly ash beads are added into a mixer with cement, sand, fly ash, silica fume, water and water reducing agent in proportion, and stirred at a speed of 60 r / min for 3 minutes to obtain ultra-high performance concrete slurry; then, modified fly ash beads and polypropylene fibers are added into the mixer, and stirred at a speed of 120 r / min for 3 minutes to obtain internally cured and self-repairing ultra-high performance concrete; after casting and forming for 1 day, the mold is removed and then cured at a temperature of 20±2°C.
[0076] Example 3
[0077] The difference between this embodiment and Embodiment 2 is that the raw materials include the following raw materials in proportion by mass: 92 parts of etched fly ash floating beads, 195 parts of modified fly ash floating beads, 430 parts of cement, 128 parts of fly ash, 104 parts of silica ash, 950 parts of sand, 4.5 parts of water reducer, 162 parts of water and 50 parts of polyester fiber.
[0078] In this embodiment, the total mass fraction of cement, etched fly ash floating beads and modified fly ash floating beads is 717 parts, and the mass fraction ratio of etched fly ash floating beads to modified fly ash floating beads is about 0.5.
[0079] The preparation steps are the same as those in Example 2.
[0080] Comparative Example 1
[0081] The invention discloses an ultra-high performance concrete mixed with a super absorbent polymer. The materials include the following raw materials in parts by weight: 2.3 parts of commercially available super absorbent polymer (SAP), 717 parts of cement, 128 parts of fly ash, 104 parts of silica fume, 950 parts of sand, 4.5 parts of a water reducing agent, 162 parts of water and 50 parts of polypropylene fiber.
[0082] The difference between this comparative example and Example 2 is that the etched fly ash floating beads and modified fly ash floating beads in Example 2 are replaced with cement in the same mass fraction. This is because both cement and floating beads have certain gelling activity and play a gelling role.
[0083] The preparation method and curing method are the same as those in Example 2. SAP and fiber are added to the wet material in the mixer after the first stirring and stirred evenly.
[0084] Comparative Example 2
[0085] The invention discloses an ultra-high performance concrete without etched fly ash floating beads or super absorbent polymer. The materials include the following raw materials in parts by weight: 717 parts of cement, 128 parts of fly ash, 104 parts of silica fume, 950 parts of sand, 4.5 parts of water reducer, 162 parts of water and 50 parts of polypropylene fiber.
[0086] The difference between this comparative example and comparative example 1 is that no SAP is added.
[0087] The preparation method and curing method are the same as those in Example 2.
[0088] Comparative Example 3
[0089] The invention discloses an internally cured ultra-high performance concrete, wherein the raw materials include the following raw materials in parts by weight: 48 parts of etched fly ash floating beads, 670 parts of cement, 128 parts of fly ash, 104 parts of silica fume, 950 parts of sand, 4.5 parts of water reducing agent, 162 parts of water and 50 parts of polypropylene fiber.
[0090] The difference between this comparative example and Example 2 is that modified fly ash floating beads are not added, but the modified fly ash floating beads are replaced by cement in the same mass fraction.
[0091] The preparation method is the same as that in Example 2.
[0092] Comparative Example 4
[0093] A self-repairing ultra-high performance concrete, comprising the following raw materials in parts by weight: 96 parts of modified fly ash floating beads, 662 parts of cement, 128 parts of fly ash, 104 parts of silica fume, 950 parts of sand, 4.5 parts of water reducer, 162 parts of water and 50 parts of polypropylene fiber.
[0094] The difference between this comparative example and Example 2 is that no etched fly ash floating beads are added, and the etched fly ash floating beads are replaced by cement of the same mass fraction.
[0095] The preparation steps are the same as those in Example 2.
[0096] Performance Testing
[0097] The ultra-high performance concrete in each comparative example and embodiment was prepared into a test piece, and its expansion was tested during the preparation process, and its shrinkage value was measured during the curing process to obtain Figure 2 The shrinkage value-curing time curve shown in the figure was used to count the number of cracks, and the compressive strength was tested at the set curing time. The performance test results are shown in Table 1.
[0098] Table 1
[0099]
[0100]
[0101] It can be seen from Table 1 that the treated ultrafine fly ash beads significantly improve the performance of UHPC. The ultra-high performance concrete shown in Example 2 and Example 3 has a compressive strength of 136.7MPa and 124.2MPa, respectively, which is much higher than that of Comparative Example 1 (112.3MPa) and Comparative Example 2 (123.6MPa). This shows that the ultrafine fly ash beads treated with chemical etching and modification can effectively promote the hydration reaction of cement-based materials, increase hydration products, and thus improve the density and strength of concrete.
[0102] Secondly, the advantages of processed ultra-fine fly ash beads are also reflected in the control of early shrinkage of concrete. Figure 2 As shown, the early shrinkage values of Examples 2 and 3 are significantly lower than those of Comparative Example 2, because the pore structure of the ultrafine fly ash floating beads can absorb and slowly release water, effectively slowing down the early self-shrinkage caused by the hydration reaction; in particular, the shrinkage value of Example 3 is comparable to that of Comparative Example 1 with SAP added, reflecting excellent anti-shrinkage performance. The modified ultrafine fly ash floating beads can break the surface film to release water when cracks are generated, undergo secondary hydration, and fill the cracks, thereby reducing the number of cracks.
[0103] Again, by comparing Examples 2 and 3 with Comparative Example 1, we can see the advanced nature of the method of the present invention: compared with the traditional SAP internal curing method (Comparative Example 1), the present invention not only has better effects in reducing self-shrinkage and crack self-repair, but also can improve the mechanical properties of concrete, which is difficult to achieve in Comparative Example 1; in addition, compared with the ultra-high performance concrete (Comparative Example 2) that has not been internally cured, Examples 2 and 3 in which ultra-fine fly ash beads are added to perform internal curing on the concrete have also been significantly improved in terms of anti-permeability performance, demonstrating the importance of internal curing for improving the performance of ultra-high performance concrete.
[0104] By comparing Example 3 with Comparative Examples 3 and 4, it can be seen that the addition of etched ultrafine fly ash floating beads or modified ultrafine fly ash floating beads alone can improve the performance of concrete to a certain extent, but compared with the synergistic effect of adding two types of ultrafine fly ash floating beads at the same time, the extent is limited and cannot reflect sufficient advantages.
[0105] In summary, the present invention proposes an internal maintenance and self-repair method for ultra-high performance concrete based on ultra-fine fly ash floating beads by chemically etching and modifying the ultra-fine fly ash floating beads, which not only effectively utilizes industrial waste and reduces environmental pollution, but also significantly improves the mechanical properties and durability of ultra-high performance concrete. In addition, the amount of cracks generated is small, the impermeability level is high, and underground projects in water-rich strata can be applied, including the construction of: the main structure of underground rail transit stations, tunnel lining structures, or water diversion tunnels for water conservancy projects. This internal maintenance and self-repair method based on ultra-fine fly ash floating beads provides new ideas for the research and development and application of ultra-high performance concrete materials, and demonstrates significant technical innovation and application prospects.
[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An internally cured and self-repairing ultra-high performance concrete, characterized in that: It is prepared from the following raw materials in parts by weight: 430-574 parts of cement, 123-133 parts of fly ash, 99-109 parts of silica fume, 945-955 parts of fine aggregate, 4-5 parts of water reducer, 157-167 parts of water, 45-55 parts of fiber, 48-92 parts of etched fly ash floating beads and 96-195 parts of modified fly ash floating beads; The method for preparing the modified fly ash floating beads comprises the following steps: S1. After etching the fly ash floating beads with a corrosive solution, the fly ash floating beads in the corrosive solution are collected, washed, dried, filtered and dried to obtain etched fly ash floating beads; S2. After the etched fly ash floating beads are fully saturated with water, the saturated etched fly ash floating beads, cement, silica fume, a water reducing agent and water are mixed and stirred to obtain a modified fly ash floating bead slurry; S3, spreading the modified fly ash floating beads slurry flat and drying it to obtain the modified fly ash floating beads, and sieving the modified fly ash floating beads to obtain the modified fly ash floating beads; The total mass fractions of cement, etched fly ash floating beads and modified fly ash floating beads are set values, which are 712~722 parts.
2. The internally cured and self-repairing ultra-high performance concrete according to claim 1, characterized in that: The cement is 52.5 ordinary Portland cement, which has good compatibility with polycarboxylic acid water reducer; The mass percentage of silicon dioxide in silica fume is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 ; The fly ash is Class I fly ash, with a burning vector less than 3.0% and a specific surface area greater than 1000cm 2 / g; the ingredients include silicon oxide and aluminum oxide; The fine aggregate is river sand or quartz sand, with a fineness modulus of 2.3~3.0, a particle size of 0.075~0.35mm, and an average particle size of 0.2mm; The water reducing agent is a polycarboxylate water reducing agent; The fibers are one or more of polypropylene fibers and polyester fibers, and the fiber shape is wavy and the length is 6 mm to 12 mm.
3. The internally cured and self-repairing ultra-high performance concrete according to claim 1, characterized in that: In the modified fly ash floating beads, the particle size of the etched fly ash floating beads is 10-200 μm, and the content of silicon dioxide is greater than 50%; The cement is 52.5 ordinary Portland cement; The mass percentage of silicon dioxide in silica fume is not less than 97%, the volcanic ash activity index is greater than 95%, and the specific surface area is greater than 21.0m 2 / g, density is 2.20g / cm 3 .
4. The internally cured and self-repairing ultra-high performance concrete according to claim 1, characterized in that: In S1, the corrosion solution is obtained by compounding an acid solution with a soluble fluoride; The preparation method in S1 comprises: S1-1, prepare a hydrofluoric acid corrosion solution using 1.0M NH4F and 1.2M HCL, immerse the dry fly ash floating beads in the corrosion solution, stir and let stand, then collect the corroded fly ash floating beads that sink to the bottom; S1-2, the corroded fly ash floating beads that have settled to the bottom are rinsed with clean water and dried, and then placed in clean water, stirred and separated, and filtered to remove the damaged floating beads in the lower layer and the floating beads filled with debris inside, and the perforated floating beads in the upper layer are collected, and then the washing-drying-stirring in clean water-filtering are repeated for multiple times to obtain the etched fly ash floating beads to be dried; S1-3, vacuum drying the etched fly ash floating beads to be dried to obtain etched fly ash floating beads; In S1-1, the dry fly ash beads are immersed in the corrosion solution and stirred at a speed of 120-150 rpm for 8-10 minutes; In S1-2, the corroded fly ash beads in the lower layer are collected, rinsed continuously with clean water, repeated 5 to 8 times, and then placed in an oven at 110°C for 24 hours; the dried fly ash beads are placed in clean water, stirred with a stirrer at a speed of 120 to 150 rpm for 6 hours, and then filtered with a filter screen to retain the perforated beads on the upper layer.
5. The internally cured and self-repairing ultra-high performance concrete according to claim 1, characterized in that: In S2, The saturation method includes: placing the etched fly ash beads into a container, keeping the water level higher than the surface of the beads, stirring at a speed of 20-50 r / min for 8-10 minutes, and standing for 24-48 hours; In S2, the raw materials are mixed in the following proportions by weight: 160-180 parts of cement, 35-40 parts of saturated fly ash beads, 20-30 parts of silica fume, 80-120 parts of water and 2-2.5 parts of water reducing agent; The water reducer is a polycarboxylic acid-based high-performance water reducer with a pH value of 7.5 and a water reduction rate of more than 30%; In S2, a stirrer is used for stirring, the stirring speed of the stirrer is 120-150 r / min, and the stirring time is 90-120 s; In S3, the filtration mesh number is 200 meshes.
6. A method for preparing an internally cured and self-repairing ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: S4, mixing cement, fly ash, silica fume, fine aggregate, etched fly ash floating beads and water mixed with a water reducing agent to obtain a first mixed slurry; S5, adding modified fly ash floating beads and fibers to the first mixed slurry, stirring and mixing, to obtain a second mixed slurry; S6. Casting and curing the second mixed slurry to obtain internally cured and self-repairing ultra-high performance concrete.
7. The preparation method according to claim 6, characterized in that: In S4, the raw materials are added into a mixer and stirred at a speed of 60 r / min for 3 min to obtain a first mixed slurry; In S5, the mixer is stirred at a speed of 120 r / min for 3 min to obtain a second mixed slurry; In S6, standard curing is adopted, the formwork is removed after pouring for 1 day, and the curing is carried out at a temperature of 20±2℃.
8. Use of the internally cured and self-repairing ultra-high performance concrete according to any one of claims 1 to 5 and / or the internally cured and self-repairing ultra-high performance concrete prepared by the preparation method according to any one of claims 6 to 7 in underground engineering in water-rich strata.
Citation Information
Patent Citations
Concrete self-repairing fine aggregate as well as preparation method and application thereof
CN116730645A